Extractives, holocellulose, α-Cellulose, lignin and ash Ccntents in cultivated tropical bamboo gigantochloa brang, G. levis, G. scortechinii and G. wrayi - Razak Wahab; Mohd Tamizi Mustafa; Mahmud Sudin; Aminuddin Mohamed; Shafiqur Rahman; Hashim W. Samsi; Izyan Khalid (Maxwell Scientific Organization, 2013)
This paper studied the chemical composition of cultivated 3 year-old tropical bamboo Gigantochloa brang, G. levis, G. scortechinii and G. wrayi especially in the extractives, holocellulose, α-cellulose, lignin and ash contents. The comprehensive knowledge of the chemical components in the bamboo species will facilitate the use of the materials in the forestry industrial sector and help to enhance their utilization in the chemical and bio-chemical related industry. The chemical compositions in cultivated 3 year-old bamboo culms of these species were studied. The chemical compositions of bamboo were determined in accordance with the standards outlined in TAPPI test methods. The culms exhibited different chemical composition in the contents of extractives, holocellulose, α- cellulose, lignin and ash between the bamboo species, location in the culms and position at the nodes and internodes. The extractives content of G. brang, G. levis, G. scortechinii and G. wrayi were 8.30, 9.23, 8.00 and 8.62%, respectively. The holocellulose content for G. levis were 85.08%, G. wrayi 84.53%, G. brang 79.94% and G. scortechinii 74.62%. The α-cellulose were higher in G. brang (51.58%), followed by G. scortechinii (46.87%), G. wrayi (37.66%) and G. levis (33.80%). The lignin contents were higher in G. scortechinii (32.55%), G. wrayi (30.04%), G. levis (26.50%) and lowest in G. brang (24.83%). The ash content were 2.83% in G. scortechinii, 2.83% in G. levis, 1.29% in G. brang (1.25%) and 0.88% in G. wrayi.